Analysis of the Influence of Job Characteristics on Employee Performance with Motivation as an Intervening Variable among Employees at Cafe Sawah Pujon Kidul - Harisandi, Humam Fadhil; Nurhasanah, Siti; Fitriasari, Fika (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The purpose of this research is to examine the job characteristics, motivation, and performance of employees. This research was conducted on employees of the Pujon Kidul rice field café with a total of 68 respondents. With the technique of using the total sampling technique. Using a quantitative approach. The data analysis technique uses path analysis and the SPSS 25 program. In this study, it shows that job characteristics have a good range of scales. Motivation has a high scale range and employee performance has a high scale range. The results of this study indicate that job characteristics have a significant influence on employee performance. Characteristics have a significant effect on work motivation. Motivation has a significant effect on employee performance and job characteristics have a significant effect on employee performance through work motivation.